12x+5x=6(x+2)

Simple and best practice solution for 12x+5x=6(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+5x=6(x+2) equation:



12x+5x=6(x+2)
We move all terms to the left:
12x+5x-(6(x+2))=0
We add all the numbers together, and all the variables
17x-(6(x+2))=0
We calculate terms in parentheses: -(6(x+2)), so:
6(x+2)
We multiply parentheses
6x+12
Back to the equation:
-(6x+12)
We get rid of parentheses
17x-6x-12=0
We add all the numbers together, and all the variables
11x-12=0
We move all terms containing x to the left, all other terms to the right
11x=12
x=12/11
x=1+1/11

See similar equations:

| v^2-9v+44=0 | | (x+4)/(4)-(3x-12)/(10)=1 | | (2y^-1)-(16y^-(1/2))+30=0 | | (7-6y)=3y•4-47 | | (3y^-1)-(13y^-(1/2))+14=0 | | 3y^-1-13y^-1/2+14=0 | | 7x+18-4x+27=3x+3x-12 | | 3p+1=13p | | 5-z/53=2 | | 4x+9-15+2x=8x+2x-10+8 | | 40x+100=500 | | 8+t/3=6 | | 0=3x^2-64 | | 6+3p=93 | | r−8.52+4.62=2.3r | | x+3x=9700 | | 172=9r | | 5m+8m+10m=180 | | 2+3j-9j=11 | | 2(3)^4x=30 | | 10x-1=15-16x | | 1997=-2x+40 | | 5(g-2=3(g+2 | | 5x+5=0.2+ | | 8y=2+50 | | 1997=-x+40 | | 7x-2=4x+17 | | 5x+5=2/10+29 | | 12.5-1.5y=8 | | 1997=-3x+40 | | 1/6x+1/7x=13 | | (3y+6)=90 |

Equations solver categories